2014
DOI: 10.1111/febs.12948
|View full text |Cite
|
Sign up to set email alerts
|

Activation of T‐LAK‐cell‐originated protein kinase‐mediated antioxidation protects against focal cerebral ischemia–reperfusion injury

Abstract: T-LAK-cell-originated protein kinase (TOPK), a MAPKK-like kinase, is crucial for neural progenitor cell proliferation; however, the function of TOPK and the molecular mechanism underlying cerebral ischemia-reperfusion injury remains unknown. Therefore, we investigated the role of TOPK in experimental stroke. Sprague-Dawley rats underwent transient middle cerebral artery occlusion (tMCAO) and reperfusion, and TOPK small interfering RNA (siRNA) was delivered by intracerebroventricular injection at the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The mechanisms responsible for cerebral I/R injury are multi-facial. Among them, oxidative stress is believed to play a key role in brain cell injury following I/R [18,19]. In this study, the ROS (H 2 O 2 ) production in the brains or NG108-15 cells was significantly increased following I/R or H/R treatment, supporting the contribution of oxidative stress to I/R or H/R injury.…”
supporting
confidence: 65%
“…The mechanisms responsible for cerebral I/R injury are multi-facial. Among them, oxidative stress is believed to play a key role in brain cell injury following I/R [18,19]. In this study, the ROS (H 2 O 2 ) production in the brains or NG108-15 cells was significantly increased following I/R or H/R treatment, supporting the contribution of oxidative stress to I/R or H/R injury.…”
supporting
confidence: 65%
“…Studies have reported that activation of GABA B receptors can enhance the phosphorylation of ERK1/2 66 , Akt and GSK-3 67 in hippocampal neurons. Recent studies have shown that increasing ERK and Akt phosphorylation plays a critical role in mediating the neuroprotective effects under cerebral ischemia 68 69 70 71 72 . ERK and Akt not only play an important role in regulating apoptosis but also have been implicated in autophagy 16 73 .…”
Section: Discussionmentioning
confidence: 99%
“…T-LAK-cell-originated protein kinase (TOPK) is involved in many biological functions, including the inhibition of apoptosis, promotion of cell growth, and antioxidation. TOPK has the ability to regulate oxidative stress: in H 2 O 2 -induced oxidative stress, TOPK is significantly activated, and p-TOPK levels begin to increase at 15 min, peak at 30-60 min, and return to basal levels at 120 min, while a TOPK inhibitor aggravates H 2 O 2 -induced oxidative stress damage (Zhao et al, 2014b). CIP promotes TOPK phosphorylation, significantly enhances TOPK activity, and reduces reperfusion injury (Zhao et al, 2014a).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 99%